2006
DOI: 10.1210/jc.2006-1442
|View full text |Cite
|
Sign up to set email alerts
|

Association between Neuromedin U Gene Variants and Overweight and Obesity

Abstract: Amino acid variants in NMU associate with overweight and obesity, suggesting that NMU is involved in energy regulation in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…NMU-25 potently suppressed glucose-stimulated insulin secretion from human islets in static batch culture assays (Figure 7H, P < 0.001 for GSIS) and islet perifusion experiments (Figure 7I–K). An NMU R165W allele that encodes a mutant peptide was previously found to co-segregate in an autosomal dominant pattern with early-onset obesity (Hainerová et al 2006). In that study, a subset of carriers displayed elevated insulin C-peptide levels; based on these findings and mutation of the highly conserved NMU C-terminal pentapeptide in this family, we reasoned that suppression of insulin secretion might be impaired by the mutant NMU R165W variant.…”
Section: Resultsmentioning
confidence: 99%
“…NMU-25 potently suppressed glucose-stimulated insulin secretion from human islets in static batch culture assays (Figure 7H, P < 0.001 for GSIS) and islet perifusion experiments (Figure 7I–K). An NMU R165W allele that encodes a mutant peptide was previously found to co-segregate in an autosomal dominant pattern with early-onset obesity (Hainerová et al 2006). In that study, a subset of carriers displayed elevated insulin C-peptide levels; based on these findings and mutation of the highly conserved NMU C-terminal pentapeptide in this family, we reasoned that suppression of insulin secretion might be impaired by the mutant NMU R165W variant.…”
Section: Resultsmentioning
confidence: 99%
“…NmU reduced their fat mass (73 ), and transgenic mice overexpressing NmU displayed reduced body weight and fat storage compared to their wild-type littermates, even on a high-fat diet (86 ). Moreover, certain genetic variants of NmU-which according to structure/function correlation appear to be devoid of or have reduced functional activity-are associated with overweight and obesity (87 ). NmU expression appears to be regulated by feeding behavior as well, because NmU concentrations in the hypothalamus are reduced by fasting (36 ).…”
Section: Energy Homeostasis and Feedingmentioning
confidence: 99%
“…Some have found that mice lacking the NMUR2 gene do not show this phenotype (218), but others have found that NMUR2-deficient mice are lean, hypophagic, and somewhat resistant to weight and fat gain on a high-fat diet (190). In humans, variants in the gene encoding pro-NMU are associated with obesity (219). This led to interest in neuromedins as a potential target for weight-loss therapy.…”
Section: Neuromedinsmentioning
confidence: 99%